Women's Malnutrition in India: The Role of Economic and Social Status. (August 2015) - Dahiya, Shikha; Viswanathan, Brinda
This study has used data from the India Human Development Survey (IHDS), 2005–06, to study the factors influencing the body mass index (BMI) of women between 20 and 40 years of age in India. BMI captures both undernutrition and over-nutrition, and a quantile regression model has been used to capture the differential impact of the explanatory variables across the wide range of its values. Variables such as per capita income, per capita consumption expenditure and wealth are important in explaining variations in BMI, but the impact varies across the quantiles. The impact of per capita consumption expenditure is greater than that of per capita income, indicating the effectiveness with which resources are converted to consumption. Higher levels of wealth status affect BMI more across all the quantiles. Women's autonomy index shows a positive impact only for higher levels of the index value, but the magnitude is very small, while caste and religion play an important role even after controlling for economic status. JEL Classification: I12, J10, O18